(untitled) (Marketing Journal, 2026)
The study systematically examined the theoretical foundations of integrating digital technologies into the production management process of textile enterprises . Within the Industry 4.0 paradigm , the functional role of IoT, ERP, artificial intelligence , and Digital Twin technologies in enhancing production efficiency was analyzed . Based on a systematic review of scientific literature and analytical reports published worldwide , the mechanisms of digital transformationʼs impact on textile manufacturing were identified . The effectiveness of digital technologies in quality control , resource optimization , and supply chain management was substantiated through empirical evidence . The main barriers to implementation - financial constraints , shortage of qualified personnel , and insufficient technological infrastructure - were identified . The research results established a theoretical basis for developing a phased strategy for implementing digital technologies in textile enterprises .